Quirky Quarks A Cartoon Guide to the Fascinating Realm of Physics - Bahr, Benjamin; Lemmer, Boris; Piccolo, Rina.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
Hard Science Doesn't Have to be Hard Do you love quantum physics, cosmology, and the humor behind the popular television show The Big Bang Theory? Have you been on the lookout for a fun, non-technical explanation of the science behind things like time travel, wormholes, antimatter, and dark energy? You$1 (Bll find all of that, and more, inside this fact-filled, cartoon-packed book. In Quirky Quarks: A Cartoon Guide to the Fascinating Realm of Physics you$1 (Bll get: The latest science behind the mysteries of our universe explained in common everyday language. A major dose of cartoons, comics, and humor. A good grasp on the often-bizarre nature of reality. Start reading and you$1 (Bll find that hard science does not have to be hard. Whether you$1 (Bre a teacher, a physicist, or just a lover of the curious, this is the book that delivers the facts in an engaging and entertaining cartoon world inhabited by two dogs, a cat, and some very quirky quarks. With cutting edge science articles by physicists Boris Lemmer and Benjamin Bahr, and drawings by cartoonist Rina Piccolo, this may be the most fun science reading you$1 (Bre likely to find out there.s
Keywords: Popular works; Physics; Popular Science; Popular Science in Physics; Physics, general; Electronic books